Straumsvík Sprouts : Cultivating a Regenerative Environment - Heiða Sigrún Pálsdóttir 1978- (2024)
Straumsvík Sprouts reimagines the industrial landscape in Straumsvík, Iceland, as a dynamic center for vertical farming, research, and community connections. In response to the escalating climate crisis and the radical change needed in our food production systems Straumsvík Sprouts aims to reduce Iceland’s food-related co2 emissions through promoting local, plant-based food production and lessening reliance on imported produce. By exploring new innovative protein sources, like algae and fungi, and focusing mostly on vertical farming the project minimizes the environmental impact associated with traditional agriculture. Furthermore, Straumsvík Sprouts encourages collaboration between local businesses and residents through a circular economy, leading to increased resource efficiency and waste reduction. The project goes beyond food production and demonstrates the potential to serve as a model for future sustainable urban development, promoting social sustainability by weaving the community back into the landscape. Public spaces, pedestrian paths, and urban gardens reconnect residents with nature and encourage social interactions, creating an engaged community. Straumsvík Sprouts strives not just to be sustainable, but to be regenerative. It aims to plant a seed of care for our planet and cultivate a thriving social ecosystem that will benefit both the environment and the local community.